Применение метода приближенного прямого моделирования при предварительных испытаниях теплообменников - Bazelev, B. P.; Bykadorov, V. V.; Efremov, V. I.; Khramova, L. F. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The proposed method makes it possible to carry out bench tests of heat exchangers using the available coolant in the equipment, which differs from that used in operation. The study shows that the error of modeling results compared to the results of heat exchanger tests within actual systems did not exceed 10%. The method has been repeatedly tested in bench trials with antifreeze on 65 heat exchangers of thermal control systems for equipment, as well as on air-oil heat exchangers used in aircraft engines AН‑140 and AН‑70 with various types of oils (Б‑3В, ЛЗ‑240, ИПМ‑10, etc.).